2017
DOI: 10.1055/s-0037-1602423
|View full text |Cite
|
Sign up to set email alerts
|

Motor Complications of Dopaminergic Medications in Parkinson's Disease

Abstract: Motor complications are a consequence of chronic treatment of Parkinson’s disease (PD) and include motor fluctuations (wearing-off phenomenon) and levodopa-induced dyskinesia. Both can have a significant impact on functionality and quality of life and thus proper recognition and management is essential. The phenomenology and temporal relationship of motor complications to the schedule of levodopa dosing can be helpful in characterizing them. There are several therapeutic approaches to motor complications, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 102 publications
(122 reference statements)
3
72
0
1
Order By: Relevance
“…No significant association was observed between motor fluctuation and the TaqIA polymorphism in a multivariate analysis, although there was an increased risk for the development of motor fluctuations related to the daily dose of levodopa, corroborating with data found by Freitas et al …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…No significant association was observed between motor fluctuation and the TaqIA polymorphism in a multivariate analysis, although there was an increased risk for the development of motor fluctuations related to the daily dose of levodopa, corroborating with data found by Freitas et al …”
Section: Discussionsupporting
confidence: 90%
“…In the present study, as previously suggested by Sharma et al the risk of dyskinesia was a consequence of an interaction among intrinsic factors, such as age, gender and genetics (patient-related) and extrinsic factors such as the use of dopamine agonists, L-DOPA dose, COMT and MAO inhibitors (medication-related). [8,9] Furthermore, in this study, an additional association was observed with the degree of disease severity. Regarding the DRD2/ANKK1 rs1800497 no significant difference was verified in relation to the development of motor fluctuation or dyskinesia in both univariate and multivariate analyses, similar to the results observed by Rieck et al [35] On the other hand, Wang et al [14] found an association with the TaqIA A1/A1 genotype with the development of motor fluctuation in a Chinese population.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations